Phenotypic responses in Caenorhabditis elegans following chronic low‐level exposures to inorganic and organic compounds. (1st February 2018) - Mugova, Fidelis; Read, Daniel S.; Riding, Matthew J.; Martin, Francis L.; Tyne, William; Svendsen, Claus; Spurgeon, David
Abstract: Responses of organisms to sublethal exposure of environmental stressors can be difficult to detect. We investigated phenotypic changes in the tissue of Caenorhabditis elegans via Raman spectroscopy, as well as survival and reproductive output when exposed to chronic low doses of metals (copper, zinc, or silver), an herbicide (diuron), and a pesticide (imidacloprid). Raman spectroscopy measures changes in phenotype by providing information about the molecular composition and relative abundance of biomolecules. Multivariate analysis was used to evaluate the significance of treatment phenotype segregation plots compared with controls. Dose‐dependent responses were observed for copper, zinc, silver, and diuron, whereas imidacloprid exposure resulted in a small response over the tested concentrations. Concentration‐dependent shifts in nematode biomolecular phenotype were observed for copper. Despite having a dose–dependent reproductive response, silver, diuron, and imidacloprid produced inconsistent biological phenotype patterns. In contrast, there was a clear stepwise change between low concentrations (0.00625–0.5 mg/L) and higher concentration (1–2 mg/L) of ionic zinc. The findings demonstrate that measuring phenotypic responses via Raman spectroscopy can provide insights into the biomolecular mechanisms of toxicity. Despite the lack of consistency between survival and Raman‐measured phenotypic changes, the results support the effectiveness of Raman spectroscopy and multivariate analysis to detect sublethal responses of chemicals in whole organisms and to identify toxic effect thresholds. Environ Toxicol Chem 2018;37:920–930. © 2017 SETAC